Pengaruh Laju Pemakanan Pada Proses Milling Baja SKD 61 Terhadap Keausan Pahat Endmill Karbida 2 Flute - Arthasasta Sharon Rumbiak; Hardy Sari Putra; M. Sobron Yamin Lubis; Erwin Siahaan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The metal-cutting process in manufacturing operations plays a crucial role in achieving a product's desired dimensions, sizes, and shapes; SKD 61 steel is widely used in the mold-making industry due to its excellent hardness properties. This study evaluates the effect of varying feed rates on tool wear during dry milling using a 2-flute carbide end mill cutter. A series of experimental tests were conducted using a manual milling machine to investigate the influence of feed rate variation on tool life. The feed rate variations used were 42 mm/min, 98 mm/min, and 230 mm/min. Other machining parameters were kept constant: spindle speed at 1320 rpm, cutting depth of 0.5 mm, and a tool diameter of 10 mm. The results showed that increasing the feed rate directly accelerated tool wear. The maximum tool wear, 0.6 mm, was reached at different times for each feed rate: 115 minutes (42 mm/min), 95 minutes (98 mm/min), and 80 minutes (230 mm/min). These findings provide valuable insights for optimizing cutting parameters to extend tool life and improve machining efficiency when working with SKD 61 steel components.